IMPLICATIONS OF MOBILE PHASE COMPOSITION AND PH ON THE CHROMATOGRAPHIC SEPARATION OF AMITRIPTYLINE AND ITS METABOLITE NORTRIPTYLINE - Buhagiar, Luana Mifsud; Scorpiniti, Manuel; Bartolo, Nicolette Sammut; Szijj, Janis Vella; Ferrito, Victor; Inglott, Anthony Serracino; Laferla, Godfrey (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Separation of tricyclic compounds sets the keystone for determining parent drug to metabolite concentration ratios and analysing impurities. The combined effects of acetonitrile composition and pH of the mobile phase on the separation of amitriptyline and nortriptyline by reversed-phase high-performance liquid chromatography (RP-HPLC) are presented. Methods: A series of RP-HPLC triplicate runs were carried out using acetonitrile and a phosphate buffer as the mobile phase and a KinetexÂ® C18 LC Column as the stationary phase using an Agilent 1260 Infinity SeriesÂ® II liquid chromatography system with UV/visible detection. The stationary phase, column temperature, injection volume and flow rate were kept unchanged during analysis. Mobile phase composition and pH were varied to observe impact on peak shape, resolution and retention time, taking into consideration green analytical chemistry aspects. Results: Optimal chromatographic outcomes were achieved when using the mobile phase made up of 35% acetonitrile and 65% buffer at a pH of 5.6. These conditions resulted in nortriptyline and amitriptyline eluting at 4.66 min and 5.92 min respectively. Increasing the organic modifier content of the mobile phase to 40% completed separation within a run time of 4 min with comparable resolution. The 2 min gained by increasing 5% acetonitrile may not be justified due to potential implications on greening laboratory practices. Conclusion: Reversed-phase chromatography embodies a simple method for the separation of compounds that are similar in structure. Attuning the percentage of organic modifier and buffer pH provides acceptable retention times, without compromising resolution between neighbouring peaks.